PENGARUH CAPITAL ADEQUACY RATIO (CAR), NON PERFORMING LOAN (NPL), NET INTEREST MARGIN (NIM), BIAYA OPERASIONAL DAN PENDAPATAN OPERASIONAL (BOPO) SERTA LOAN TO DEPOSIT RATIO (LDR) TERHADAP RETURN ON ASSETS (ROA) - Dhara Yulita VMS; Maryono Maryono; Agus Budi Santosa (Dinamika Akuntansi Keuangan dan Perbankan, 2020)
This thesis contains a study of how BPR financial ratios are Current Asset Ratio (CAR)/ Minimum Capital Requirements (KPMM), Non-Performing Loans (NPL), Net Interest Margin (NIM), Operational Costs Operating Income (BOPO), and Loans to Deposit Ratio (LDR) affects the level of profitability projected by the Return on Assets (ROA) ratio. In this study CAR/ KPMM, NPL, NIM, BOPO and LDR as independent variables, while ROA as the dependent variable. This study uses sample data from the financial statements of Rural Bank (BPR) in Semarang City registered with the Financial Services Authority (OJK) in 2016 to 2018. Sampling from the OJK website (www.ojk.go.id) and using the Purpossive method Sampling. There are 23 BPRs that meet the criteria as research samples. The sample data is processed using Microsoft Excel and SPSS 19. The analytical method used for data processing in this study is the Multiple Linear Regression Analysis Method. The results of the data processing in this study indicate that CAR / KPMM and NIM have a significant positive effect on ROA, BOPO has a significant negative effect on ROA and NPL, and LDR does not significantly influence ROA Key Wor : Rural Credit Banks (BPR), ROA, CAR/KPMM, NPL, NIM, BOPO, LDR